Bronx - změna adresy (přestavba káznice) - Janoušková, Zuzana (Vysoké učení technické v Brně. Fakulta architektury)
Bronx - změna adresy (přestavba káznice) Diplomová práce představuje architektonickou studii nového využití objektu káznice a jeho nejbližšího okolí v brněnském „Bronxu“. Káznice s kaplí Nanebevzetí Panny Marie z 18.století je významná stavba o velikosti přibližně jednoho městského bloku. Návrh zahrnuje úpravy původního objektu káznice a jeho nástavbu; odstranění nevhodných přístaveb a vytvoření nových objektů v návaznosti na káznici a veřejná prostranství. Soubor budov je řešen se zřetelem na alternativní kulturu a alternativní formy bydlení, které by měly pomoci v uzdravování romského ghetta. Nové rozmístění a velikosti objektů vytváří dvě nová náměstí. Zároveň dovolí odhalit káznici v její původní formě. Na jižní straně je navržena výšková budova jako dominanta v území.

Bronx - address substitution (reconstruction house of correction) The graduation thesis deals with an architectural study of a new utilization of the top security prison building and its sorrounding in „the Bronx“ of Brno. The prison with the chapel of the Assumption of the Virgin from the 18th century is a significant building of about one city block large. The project includes the modification of the original prison building and its extension, the removal of the unsuitable parts of the building and building of new objects connected to the prison and public places. The group of buildings has been designed with the regard to the alternative culture and forms of living places, which would lead to healing of the Roman ghetto. New arrangement and size of objects form two new squares. It reveals the prison in its original shape at the same time. On the south site there is a tall building designed as a dominating feature of the area.
Bronx - address substitution (reconstruction house of correction)
Keywords: Bronx - změna adresy (přestavba káznice); Bronx - address substitution (reconstruction house of correction)